2005
DOI: 10.1021/ma047973u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and CO2 Solubility Studies of Poly(ether carbonate)s and Poly(ether ester)s Produced by Step Growth Polymerization

Abstract: Poly(ether carbonate)s (PEC) and poly(ether ester)s (PEE) were synthesized by step growth polymerization, and the reaction conditions were optimized. The solubility of the polymers in CO 2 was then evaluated using two methods: (i) observation of the cloud point and (ii) gravimetric extraction. Our results suggest that it is difficult to give an exact description of the solubility profiles for these polymers using cloud points alone, particularly in cases where there is a broad distribution of molecular weights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…A number of studies have been conducted on the synthesis of poly(ether carbonate)s. Poly(ether carbonate)s, with controlled composition, were prepared from oligomeric PPG diols with carbonyldiimidazole or diglycoyl chloride 10. A polycarbonate block with a polyether block containing appropriate reactive end groups leads to a block poly(ether carbonate).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted on the synthesis of poly(ether carbonate)s. Poly(ether carbonate)s, with controlled composition, were prepared from oligomeric PPG diols with carbonyldiimidazole or diglycoyl chloride 10. A polycarbonate block with a polyether block containing appropriate reactive end groups leads to a block poly(ether carbonate).…”
Section: Introductionmentioning
confidence: 99%
“…8,12 Unfortunately, a direct comparison to experiment is hampered by the complexity of the parameter space for this systems, that is, the solubilities of the PEO and CARB-PEO polymers depend on temperature, molecular weight, carbonyl content, microstructure (statistical, alternating, or block copolymers), and nature of the terminal group (e.g., -OH, -O-alkyl, or -O-CO-CH 3 ). 8,9,12 Sarbu et al 9 reported a similar cloud point pressure (at ambient temperature) for a CARB-PEO copolymer with a total of about 103 repeat units and a carbonate fraction of 34% and a PEO homopolymer with 16 repeat units (i.e., a strong enhancement of the solubility). Tan et al 12 observed a dramatic decrease in the cloud point pressure for alternating copolymers of similar molecular weight (about 8200 g/mol) when the carbonate content is increased from 8.8 to 12.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The negative Gibbs free energy of transfer for the carbonate repeat unit signals its favorable solvation in supercritical CO 2 , thereby leading to a solubility enhancement for the molecular weights and compositions studied here. However, it should be noted that our simulation looks at a block copolymer architecture, and additional simulations that probe the link between molecular sequence and solubility would be very useful (i.e., computing the incremental Gibbs free energy for a carbonate unit that is sandwiched between two EO units as found in alternating copolymers 12 ) but are outside the scope of this study. Figure 3 depicts the RDFs and corresponding number densities for the carbonyl or ether oxygen with the carbon of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Cloud point in scCO2 can be defined as the pressure in which the polymer starts to precipitate out from the solution at a given temperature 47 . Cloud points of synthesised statistical/block copolymers were determined by using high pressure variable volume view cell equipment that was produced by University of Nottingham 48 .…”
Section: Cloud Point Measurements Of the Diblock Copolymersmentioning
confidence: 99%